Peran Guru dalam Meningkatkan Efektivitas Pembelajaran di SDN Karyasari 1 : Perspektif Literatur dan Studi Kasus - Neneng Tanjihah (Konstanta : Jurnal Matematika dan Ilmu Pengetahuan Alam, 2024)
This study aims to examine the role of teachers in enhancing the effectiveness of learning at SDN Karyasari 1 through a literature review and case study approach. The teachers at SDN Karyasari 1 were analyzed regarding the strategies and efforts they undertake to improve the quality of classroom learning. Data were collected through interviews, observations, and document studies. The results show that teachers play a significant role in creating a conducive learning environment, managing the classroom effectively, and implementing diverse and engaging teaching methods. Factors supporting learning effectiveness include teacher competence, student motivation, and the use of learning media tailored to students' needs. This study provides valuable insights into the importance of teachers' roles in the success of the learning process at elementary schools.